Theoretical study on second-harmonic generation of focused vortex beams. (5th February 2018) - Tang, Daolong; Wang, Jing; Ma, Jingui; Zhou, Bingjie; Yuan, Peng; Xie, Guoqiang; Zhu, Heyuan; Qian, Liejia
Abstract: Second-harmonic generation (SHG) provides a promising route for generating vortex beams of both short wavelength and large topological charge. Here we theoretically investigate the efficiency optimization and beam characteristics of focused vortex-beam SHG. Owing to the increasing beam divergence, vortex beams have distinct features in SHG optimization compared with a Gaussian beam. We show that, under the noncritical phase-matching condition, the Boyd and Kleinman prediction of the optimal focusing parameter for Gaussian-beam SHG remains valid for vortex-beam SHG. However, under the critical phase-matching condition, which is sensitive to the beam divergence, the Boyd and Kleinman prediction is no longer valid. In contrast, the optimal focusing parameter for maximizing the SHG efficiency strongly depends on the vortex order. We also investigate the effects of focusing and phase-matching conditions on the second-harmonic beam characteristics.